PENGEMBANGAN LIFE SKILL SANTRI DI PONDOK PESANTREN AL-URWATUL WUTSQO JOMBANG - Achmad Abdul Munif (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2019)
Historically, pesantren are multifunctional educational institutions. It became a stronghold as well as the center of Islamic. There is no definitive data about the initial presence of pesantren in the archipelago. This study aims to describe how the implementation of life skills development in PP-UW, as well as factors that are obsatacle and supporting the program. This research uses qualitative method, data collected by interview and observation, the data then analysed by reduction, data display, and verification. The research result is life skill kinds in al Urwatul Wutsqo boarding scholl are personal, social, academic, and vocational skill. It is started with planning while setting the goal done by the leader and teachers. In implementing, they use learning strategies oriented towards student activeness and contextual learning models. To evaluate the program, they use context, input, process and product/outcome evaluation (CIPP) model. The obstacle factors are lack of complete infrastructure in the form of tools for work practices, discipline among students, and lack of skilled instructors, besides, funding is also influenced it. The supporting factors are the activeness of leaders, religious teachers who are competent, and varied methods used.